Identification of gold binding peptides using a phage display peptide library - Chua, K.H.; Lau, T.P.; Rahman, N.A.; Wong, S.K.; Othman, R.Y. (2008)
Micron gold particles were used in this study to assess potential protein-metal interactions. A total of three rounds of biopanning with the gold particles were carried out using a phage display peptide library. In this system, the random 12-residue peptides are displayed at the N-terminus of pIII gene of M13mp19 phage. Peptides that bind to gold particles with high affinity were amplified after each round of the biopanning process. After 3 rounds of biopanning selection, five clones were isolated and the affinities of the clones were estimated and confirmed by ELISA analysis. The deduced peptide sequence, VGAHYNYGVIML was obtained through translation of DNA sequencing data. Overall, the ELISA results showed strong binding affinity of this peptide towards gold.